Implicații ale privatizării asupra calității vieții - Barbu, Gheorghe (Calitatea Vieții, 1990)
The development of private property, as a process through which the market economy is achieved, has opposite effects upon the quality of life: on the one hand it stimulates the personal concern for developing activities with a maximum efficiency and it guarantees a large variety of goods and services ; but on the other hand, as a result of competition and of the specific economic law, it generates significant differences between the living conditions of various social groups. The opposite consequences take various forms, among which an exacerbated individualism can be noticed on the moral plane.